2021
DOI: 10.1002/etc.5172
|View full text |Cite
|
Sign up to set email alerts
|

Particle‐Specific Toxicity of Copper Nanoparticles to Soybean (Glycine max L.): Effects of Nanoparticle Concentration and Natural Organic Matter

Abstract: For the soluble metallic nanoparticles (NPs), which forms (particles [NP (particle) ] vs. dissolved ions [NP (ion) ]) are the main cause of toxicity of the NP suspension (NP (total) ) remains uncertain. In the present study, soybean was exposed to Cu NPs in a hydroponic system to determine how natural organic matter (NOM; 10 mg/l) and concentration of Cu NP (total) (2-50 mg/l) affect the relative contributions of Cu NP (particle) and Cu NP (ion) to the overall toxicity. We found that NOM mitigated the phytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…A relatively high uptake of Cu and altered nutrient quality in soybean (Glycine max) grown in agricultural soil amended with CuNPs (Xiao et al, 2022) were reported. Moreover, natural organic matter increased the dissolution of CuNPs, and mitigated the phytotoxicity of CuNPs more significantly than that of Cu salt (Xiao et al, 2021). The increasing use of Cu-based NPs in agricultural, industrial and environmental applications will undoubtedly lead to their spread in terrestrial ecosystems (Bakshi and Kumar, 2021).…”
Section: Tablementioning
confidence: 99%
“…A relatively high uptake of Cu and altered nutrient quality in soybean (Glycine max) grown in agricultural soil amended with CuNPs (Xiao et al, 2022) were reported. Moreover, natural organic matter increased the dissolution of CuNPs, and mitigated the phytotoxicity of CuNPs more significantly than that of Cu salt (Xiao et al, 2021). The increasing use of Cu-based NPs in agricultural, industrial and environmental applications will undoubtedly lead to their spread in terrestrial ecosystems (Bakshi and Kumar, 2021).…”
Section: Tablementioning
confidence: 99%
“…[ 13 ] Similarly, chemical‐based CuNPs at 500 mg kg −1 soil significantly reduced the incidence of tomato bacterial wilt by ≈37% through inhibiting the growth and biomass of the pathogen Ralstonia solanacearum . [ 14 ] Earlier studies frequently reported phytotoxic effects of Cu‐based nano‐ or bulk‐agrochemicals on the morpho‐physiological traits of different plant species; for example, Cucurbita pepo , [ 15 ] Coriandrum sativum , [ 16 ] Glycine max , [ 17 ] Mentha spicata , [ 18 ] and Cucumis sativus . [ 19 ] However, bio‐NPs have inherently reduced toxicity and greater biocompatibility, often outperforming their chemically synthesized counterparts.…”
Section: Introductionmentioning
confidence: 99%